Strategic ESG Legitimacy Model: Integrating SWOT Analysis and GRI Indicators to Assess Corporate Sustainability Performance - Evana Pasaribu; Ressa Uli Patrissia (Santoso Academy Network, 2026)
As one of the largest coal mining companies in Indonesia, PT ABC Tbk faces demands not only to maintain business performance but also to ensure sustainability practices align with international standards. Its 2024 sustainability report serves as the basis for evaluating the company's ability to manage environmental, social, and governance (ESG) issues. Using qualitative methods based on case studies and a literature review, the analysis employed a SWOT framework informed by material topics from the Global Reporting Initiative (GRI). The study results indicate that the company's sustainability performance remains average, reflected in scores of 2.16 for internal factors and 2.24 for external factors. These findings highlight weaknesses that need to be addressed and also provide opportunities for the company to strengthen its sustainability strategy, optimize existing potential, and anticipate future threats.